Decisions Taken by Various Committees and the General Council, 1-4 May 1926 (page 4)
1926-05-04 "Decisions Taken by Various Committees and the General Council, 1-4 May 1926 (page 4)" [g0563004.jpg], 1-4 May 1926, Trades Union Congress